Contemporary approach of using the orthodontic mini-implant in the temporary rehabilitation: case report (Research, Society and Development, 2023)
The aim of this study was to highlight the contemporary approach of using the orthodontic mini-implant associated with the provisional crown in the temporary rehabilitation in cases of permanent anterior tooth loss in young patients. An updated literature review was performed to support and complement the case report of a patient aged 10 years and 5 months, diagnosed with ankylosis and external root resorption of tooth 21. Orthodontic and surgical treatment was performed in three steps: alignment of upper arch permanent teeth with correction of the midline, obtaining space in the region of tooth 21; surgical removal of tooth 21; fixed provisional rehabilitation with orthodontic mini-implant and temporary tooth crown. The conclusion was that the versatility of orthodontic mini-implants allows their use in the temporary rehabilitation of permanent anterior teeth of patients in the growth phase or with residual growth potential, with rapid restoration of function and aesthetics, and mainly, preservation of the alveolar bone, as in the case presented.